The paradox of organizational learning: lesson learned between constructivism and model simulation - Atmoko, Andreo Wahyudi (Technium Social Sciences Journal, 2023)
Knowing Organization model ensures organizations can perform better in any environment. This thesis is explored further using ethnometodology to search the characteristics of organizational learning, and using the thesis of two generic structures of system dynamics to find where organizational learning paradox is. Then, through a computer simulation model the paradox impact is simulated. These two methods inspire each other in exploration of the factors affecting organizational learning and their embedded paradox due to the coexistence of reinforcing and balancing causality loop.